KESULITAN BELAJAR MATEMATIKA DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIS PADA SISWA KELAS VII SMP NEGERI 1 PAMUKAN SELATAN - Radiatul Adawiah; Hartini Hartini (STKIP Paris Barantai, 2018)
Abstract This research is a qualitative research that is descriptive, that is the data collected is not numbers, can be in the form of words or description of something. This study aims to describe student learning difficulties based on indicators of mathematical reasoning ability in class VII A SMP Pamukan Selatan 1. This research instrument is the researcher himself who is the main instrument, and the supporting instruments of this instrument are writing equipment, as well as handphones. Data collection techniques in this study include: 1) Observation (observation), 2) Test (Answering Questions), 3) Interview (Question and Answer) , 4) Documentation (supplementary data). This research instrument is the researcher himself who is the main instrument, and the supporting instruments of this instrument are writing equipment, as well as handphones. Data collection techniques in this study include 1) Observation (observation), 2) Test (Answering Questions), 3) Interview (Question and Answer), 4) Documentation (supplementary data). Based on the results of research Mathematics learning difficulties in terms of mathematical reasoning abilities. Subjects with high ability and moderate tend to use their mathematical reasoning skills in working on the problem, while low-ability subjects tend not to use their mathematical reasoning skills in working on questions. Based on the results of research Mathematics learning difficulties in terms of mathematical reasoning abilities. Subjects with high ability and moderate tend to use their mathematical reasoning skills in working on the problem, while low-ability subjects tend not to use their mathematical reasoning skills in working on questions. Keywords: Learning Difficulties, Mathematics , Reasoning Ability